Netherlands Antilles : trade and integration with CARICOM (ECLAC Port of SpainTT, 2001)
Assesses the integration options facing the Netherlands Antilles vis-a-vis the Caribbean Community (CARICOM). Examines the above taking into account, inter alia, the level of trade between the Netherlands Antilles and CARICOM, the barriers to trade between the two groups of countries and the requirements for increasing trade between these countires.
Keywords: TRADE